Synthesis and optical properties of bis- and tris-alkynyl-2-trifluoromethylquinolines - Jopp, Stefan; Spruner von Mertz, Franziska; Ehlers, Peter; Villinger, Alexander; Langer, Peter (Beilstein Journal of Organic Chemistry, 2024)
Three bis- or tris-brominated 2-trifluoromethylquinolines have been successfully applied in palladium-catalysed Sonogashira reactions, leading to several examples of alkynylated quinolines in good to excellent yields. Optical properties of selected products have been studied by steady state absorption and fluorescence spectroscopy which give insights of the influence of the substitution pattern and of the type of substituents on the optical properties.
Keywords: alkynes; catalysis; fluorescence; heterocycles; palladium